Intervjuundersökning om landsbygdens krafter och mekanismer - Carlberg, Magnus (2007)
This final thesis is a basic inquiry into a countryside programme for the municipality of Hässleholm. By interviewing people who live in the countryside in the municipality of Hässleholm I've tried to get a picture of how the thoughts on development of countryside are. Trough these interviews I've also tried to find out how people on the countryside defines the concept of countryside. Using the information from the interviews I give recommendations to the municipal government on how to develop the different parts of the municipality in order to not destroy existing values and qualities. Countryside has so far been developed spontaneously and is a mix of nature and human activity. How can municipal planning be used to develop countryside into a sustainable environment?